Local Specifics of Vocabulary of Funeral and Memorial Rituals of Russian Prikamye - I. A. Podyukov; E. N. Svalova (Научный диалог)
The relevance of the study is due to the increased interest in displaying the dialectic picture of the world as the most important component of ethnic culture. The issues of local originality of nominations of funeral and memorial ritual realities in Russian dialects of the Middle Prikamye are considered. A review of modern studies of folk funeral and memorial terminology is performed. Attention is paid to the substantive side of ritual terms, their motivation, symbolism, methods of education. The results of a comparative analysis of the semantics of the studied nominations with the data of other Russian dialects are presented. The question of nominative redundancy in the studied ritual sphere is raised, which is associated with the history of the formation of Perm dialects on the basis of North Russian and Volga dialects, with the coexistence of traditional beliefs, Orthodoxy and Old Believers in the folk cultural tradition of the Kama region. It is proved that most of the details and episodes of the funeral-memorial rituals in the Kama region have a specifically local language mapping. Particular attention is paid to the description of semantic groups with pronounced regional specifics (mythologies, names of funeral clothes and shoes, food, temporal nominations, names of ritual objects). It is shown that the terminological composition of the ritual sphere in Prikamye is in many respects correlated with the all-Russian dialect terminological system, while a considerable number of purely Permian nominations related to self-development of the dialect are fixed.